The impact of informal interaction between volunteer and child from social care institution to the child‘s social network - Dunajevas, Eugenijus; Buzaitytė-Kašalynienė, Jolita (Socialinė teorija, empirija, politika ir praktika, 2006)
The impact of informal interaction between volunteer and child from social care institution to the child‘s social network is analysed in the paper. The problems of the children and the causes of the problems are presented in the first part. The theoretical strategies to alter the problems are discussed in the second part. In order to evaluate the impact the research was carried out. The structured interview method was used. The children and volunteers were the informants. The goal of interview was to explore the character and intensity of the interaction and to evaluate the changes in the social network of the children. The results of data analysis showed the changes in the child's social network, but the changes are not substantial.
Keywords: Volunteers; Children; Social care institution; Interaction; Social network